(untitled) (Ozone Therapy Global Journal, 2020)
Compartment syndrome is a very common pathology, with a higher prevalence in males, associated with trauma from exposed fractures, mainly of the tibia and forearm. Currently, there are many medical reviews, however, in this case we observe and recommend that the use of ozone therapy is effective for the treatment of patients with compartment syndrome since the treated patient evolved positively with a great improvement at the end of the treatment. Its treatment is urgent surgical, by performing fasciotomies of the affected compartments. Transradial vascular procedures have a low rate of vascular complications. The possibility of serious complications, such as compartment syndrome, makes it necessary to know this condition and its management.